2015
DOI: 10.1103/physrevlett.114.251103
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh-Energy Debris from the Collisional Penrose Process

Abstract: Soon after the discovery of the Kerr metric, Penrose realized that superradiance can be exploited to extract energy from black holes. The original idea (involving the breakup of a single particle) yields only modest energy gains. A variant of the Penrose process consists of particle collisions in the ergoregion. The collisional Penrose process has been explored recently in the context of dark matter searches, with the conclusion that the ratio η between the energy of post-collision particles detected at infini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 35 publications
4
76
0
Order By: Relevance
“…Now, it can be used for extremal black holes and head-on collisions. The present results can be considered as analytical proof of numerical findings of [10]. We also agree with [10] in the role of multiple scattering.…”
Section: Summary and Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Now, it can be used for extremal black holes and head-on collisions. The present results can be considered as analytical proof of numerical findings of [10]. We also agree with [10] in the role of multiple scattering.…”
Section: Summary and Discussionsupporting
confidence: 74%
“…Quite recently, one more work appeared [10] in which it was claimed that energies E of debris may be not only very large but, in principle, unbound. The results of this paper are presented in the form of figures describing numerical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…In what follows, we call this Schnittman process (scenario). Later, numerically [17] and analytically [18] it was found that if colliding particles move in opposite directions and both of them are usual, a formally infinite efficiency becomes possible (so-called super-Penrose process). The problem is, however, that a usual particle with a finite energy cannot move away from a black hole although for the critical particle this is possible ( [10], [13], [14]).…”
Section: Quarks-2016mentioning
confidence: 99%
“…As far as small N is concerned, it turned out that for collisions near black holes, amplification of the energy is restricted [13] - [15] if both initial paricles moved along ingoing trajectories. If one of particles is on an outgoing trajectory, the energy E can be quite large [16], [17] or even formally unbound [10], [18] but in the latter case very special conditions are required and it is hard to satisfy them [19], [20]. Due to recent results [21], the super-Penrose process is possible for the case of naked singularity in collisions where also small N in the point of collision is required.…”
mentioning
confidence: 99%
“…One can ask -whether or not the efficiency of the energy extraction to infinity may also become unbound? (Following [10], we will use the term "super-Penrose process".) We can exploit the same classification in terms of three parameters (N, L, ω).…”
mentioning
confidence: 99%